Sistem Pengendalian Intern Pemerintah (SPIP) Terhadap Kualitas Laporan Keuangan - Nida Andina; Nurlaila Nurlaila; Nurwani Nurwani (Journal of Management and Bussines (JOMB), 2023)
The purpose of this study was to examine the influence of the Government Internal Control System (SPIP) on the quality of financial reports produced by the Sei Nadoras Village Office, Bandar Pasir Mandoge District. This research method is associative research. This research was conducted at the Sei Nadoras Village Office, and the data used in the analysis came directly from the responses to the questionnaires that the researchers gave to the sample group which consisted of thirty workers who were the respondents. A saturation sampling approach was used in sample collection for this investigation. The results showed that the tcount value was 1.706 which was smaller than the ttable value of 2.04841, and the significance value was 0.099 which was greater than 0.05. Thus, the Government Internal Control System (SPIP) cannot explain why financial reports are of high quality. This shows that the impact cannot be calculated from the internal control system on the quality of financial reports. From the results of the study it was also found that only the risk assessment dimension contained in the government's internal control system did not affect the quality of financial reports, and only the reliable dimension was not affected by the government's internal control system. Keywords: Quality of Financial Reports, Financial Reports, Government Internal Control System (SPIP)